Upaya Optimalisasi Penghematan Subsidi Bahan Bakar Minyak (BBM) Agar Tepat Sasaran - Janita S. Meliala (Binus Business Review, 2014)
Subsidized fuel consumption continues to increase from year to year also put pressure on the state budget so that it becomes increasingly severe. This is caused by the government's energy policy tends to be adaptive and short-term oriented (myopic), so the government pays little attention to aspects of long-term autonomy of the Indonesian economy. Subsidy in the 2011 budget amounted to 33.42% of the total expenditure budget, 86% subsidy is used for energy subsidies and 64.6% the largest share of subsidies. The biggest users of fuel subsidy, is land transportation, with the classification of private vehicles, so it can be said that the subsidy is not received by the appropriate require. Related to this, the challenges that must be faced is the obligation to make a breakthrough in order to encourage domestic savings in fuel consumption and diversification in the use of non-fuel energy sources. There are three policy options as an effort to optimize the fuel subsidy savings. First, restrictions on the use of the fuel subsidy program, unfortunately the prospects of success of this policy is not good considering unprepared infrastructure and the emerging moral hazard. Second, the increase in fuel prices, the authors recommend the price increase to Rp 2000, - taking into account the effects of inflation, and financial savings, for the welfare of the people. Third, the use of CNG and new products from the fuel, this policy option can be run in the long run because it requires a longer preparation in building infrastructure.